Penerapan Jus Buah Mengkudu Terhadap Penurunan Tekanan Darah Pada Penderita Hipertensi Melalui Aplikasi Teori Peplau Di Rsud Rejang Lebong - Satria Gusti Iman Ramadhan; Tita Septi Handayani (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Hypertension is an asymptomatic condition in which abnormally high pressure in the arteries increases the risk of stroke, heart failure, heart attack, and kidney damage (Faqih in Nixon's book, 2018). Hypertension is associated with an increase in systolic or diastolic pressure, or both. Hypertension can be defined as persistent high blood pressure where the systolic pressure is above 140 mmHg and the diastolic pressure is above 90 mmHg. In the elderly population, hypertension is defined as a systolic pressure of 160 mmHg and a diastolic pressure of 90 mmHg (in Abdul Majid's book, 2018). Hypertension is an increase in blood pressure above normal, indicated by a systolic number ≥140 mmHg and a diastolic number ≥90 mmHg, which is considered prehypertension. It can then be subcategorized according to its severity. Optimal blood pressure is 120/80 mmHg, and so on, it has a range from normal blood pressure to high blood pressure (hypertension). This condition is categorized as primary or essential (almost 90% of all cases) or secondary, occurring as a result of a recognizable pathological condition, often reversible (Abimanyu Darmawan, et al, 2019) World Health Organization (WHO) data in 2015 showed that around 1.13 billion people in the world have hypertension, meaning that 1 in 3 people in the world are diagnosed with hypertension. The number of people with hypertension continues to increase every year, it is estimated that in 2025 there will be 1.5 billion people affected by hypertension and it is estimated that every year 9.4 million people die from hypertension and its complications. The method used is descriptive analysis by describing the situation or condition of the patient based on the results of care that has been carried out starting from subjective analysis to evaluation, also described the obstacles faced by the author when carrying out nursing care. The results of this study Blood pressure before giving watermelon juice obtained severe blood pressure of 2 people with blood pressure Mrs.M BP 170/100 and Mrs.S BP 180/100 and moderate blood pressure Mrs. R BP 180/100 mmhg. Blood pressure after being given Noni Fruit Juice for 3 days was obtained Mrs. M BP 150/90 NY. S BP 160/90 mmhg. The results of the application of Noni Fruit juice to hypertensive patients showed that there was an effect that there was a change in blood pressure in patients before and after the application of Noni Fruit juice to hypertensive patients.